ALGUNOS ELEMENTOS MEGAFLORISTICOS DE LA FORMACION SANTA MAXIMA, PALEOZOICO SUPERIOR, ARGENTINA (Ameghiniana, 2013)
A systematic study of a fossil megaflora form the uppermost beds ofthe Santa Máxima Formation, Upper Palaeozoic, Uspallataarea, Mendoza province, Argentina, is presented. Paracalamites australis Rigby, Ginkgophyllum sp., Cordaites sp., Cordaicarpusemarginatus Walkom and Form A have been recognized. The age is considered early Permian.